Shiite Resistance to Malaysian Religious Orthodoxy - Iulia Lumina (2017)
A closer analysis of the dynamics within the Shiite community in Malaysia would suggest that its failure to present a united front in dealing with the discrimination towards the community is an important factor that continues to negatively affect the position of Shiites.